Genotypic variation of soybean for phosphorus use efficiency and their contribution of N and P to subsequent maize crops in three ecological zones of West Africa - Abaidoo, Robert C.; Sanginga, Nteranya; Okogun, J.A.; Kolawole, G.O.; Tossah, B.K.; Diels, J. (2007)
Soybean is a relatively new crop to most African smallholder farming communities. Cultivation is expanding rapidly because of its perceived potential to enhance soil fertility through biological nitrogen fixation and its source as food and cash. High N2, fixation in promiscuous soybean genotypes is, however, likely to be constrained in low P soils where fertilizer is rarely applied. Thirteen soybean genotypes were evaluated in three ecological zones of Nigeria for (1) N2, fixation, tolerance to low soil P (0P), and response to P fertilizer application (90 kg P ha' as Rock Phosphate (RP) or 30 kg P ha' as Triple Superphosphate (TSP), and (2) the potential contribution of N and P to a subsequent maize crop. Results showed that soybean grain yields were generally low without P fertilization. Increases in grain yield in response to P application were genotype- and location-dependent and ranged from 3 to 308%within TSP treatments and from -1 6 to 1520/o within RP treatments. P exported in the grain of soybean genotypes also increased in response to P application at all the locations and ranged from 1 6 to 3270/0, depending on genotype and location. Total N exported in the grain of soybean was greater than N derived from the atmosphere (Ndfa) in most genotypes, resulting in negative N balances in almost all soybean plots with or without P application. Biomass, total P, and N content of grain of maize following soybean were also influenced by soil P and N contents at the three locations. There were few instances of significant positive N and P contributions from the previous P, application and soybean cultivation. Also, the cultivation of P-efficient and high N-fixing genotypes did not consistently result in a significantly positive N and P contribution to the subsequent maize crop.